The Relationship Of Parenting Patterns And Parental Knowledge With Speech Delay In Preschool Age Children At Hermina Padang Hospital 2023 - Waldatul Hamidah; Febrina Febrina (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
WHO 2021 reports that more than 300 million children under 5 years of age do not fulfill their development potential and most of them are children living on the Asian and African continents. Data from Hermina Hospital, the prevalence of Speech Delay in 2023 is 150 cases. In one day of research, 15 respondents were obtained. The aim of this research was to determine the relationship between parenting patterns and parental knowledge and speech delay in preschool-aged children at Hermina Hospital. Padang.This type of research uses quantitative methods with a cross sectional analytical design. The research was conducted in March – August 2023 at Hermina Padang Hospital. The research population was all mothers who had preschool children aged 3-5 years at Hermina Padang Hospital. The sampling technique was Accedental Sampling. Data collection used primary and secondary data. Univariate analysis used descriptive statistical tests and Bivariate analysis used the chi square test.The results of this research are based on the results of the Chi square test (α= 0.005) showing that there is no significant relationship between Parenting Patterns (p-value = 0.188) and there is a significant relationship between Parental Knowledge (p-value 0.032) and Speech Delay.It was concluded that there was still a lack of maternal knowledge about the importance of parenting styles and parental knowledge in children's growth and development. It is hoped that from the results of this research, parents can pay more attention to children's growth and development and that health workers can serve as a reference for improving services in reducing the incidence of speech delays.